La pérdida del monopolio en el ejercicio de la acción penal y los límites constitucionales de su regulación en Colombia. (2013)
This article conducts a thoughtful analysis of the legislative act 6th 2011 by which it is authorized the exercise of private prosecution in Colombia. This analysis is specifically to clarify the relationship between the private prosecution and adversarial litigation system. At the same time, analyzes the constitutional limits that the new constitution would impose the legislative to regulate such institution. To do this, we will study the concepts of legal asset, harmfulness and victim status, as indicated by the most qualified national and foreign doctrine, case law, and the text of the relevant national laws.